Starch in ruminant diets : a review (2016)
ABSTRACT: starch is an important energy source for ruminants nutrition. This carbohydrate is often used to improve rumen fermentation, optimizing digestion of structural carbohydrates and increasing protein flow to the small intestine. Microbial and digestive enzymes are involved in starch digestion, generating products that can positively or negatively affect animal performance and health, depending on the starch contents of the diet. Objective: to describe the basic characteristics of starches, the factors affecting its nutritional availability, and its effects in ruminants. Conclusion: a number of factors affect starch digestibility, including granule size, amylose/amylopectin ratio, proportion of farinaceous and vitreous endosperm, presence of starch-lipid and starch-protein complexes, and physical-chemical processing of the feed. Ingestion of large amounts of starch can trigger ruminal acidosis. However, its rational use in the diet has positive effects on methane emissions, and in milk yield and composition.